Gen Z Beraksi Di SMA Negeri 6 Tangerang Selatan: Membangun Masa Depan Bersih Tanpa Korupsi - Santi Rimadias; Sausan Nabila; Ariesyah Pratiwi; Kayla Ramadhani; Alyaa Alyaa; Wulan Wiranatakusumah; Nuansa Khatulistiwa (Jurnal Pengabdian Sosial, 2026)
Corruption is a serious problem that can hinder national development and undermine the social, economic, and moral well-being of society. Therefore, instilling anti-corruption values ​​from an early age is a crucial step in developing a young generation with integrity. This community service activity aimed to increase students' understanding and awareness of the importance of anti-corruption behavior through outreach activities at SMA Negeri 6, South Tangerang City. The activities were conducted face-to-face with 40 10th-grade students. The implementation method included material presentations, interactive discussions, question-and-answer sessions, and an educational game based on Quizizz. The material presented covered the definition of corruption, the causes and impacts of corruption, the values ​​of integrity, and the role of the younger generation in preventing corruption. The results showed that students enthusiastically participated actively in the discussions and educational games. Evaluation using Quizizz showed that 95% of students were able to answer questions correctly, indicating an increased understanding of the material presented. This activity demonstrates that anti-corruption outreach using an interactive and educational approach is effective in instilling the values ​​of honesty, responsibility, and integrity in the younger generation. Therefore, similar activities need to be carried out continuously as an effort to build an anti-corruption culture from an early age.